The effect of finger print absence and certification on the teachers performance - Rosa, Diana; Kristiawan, Muhammad; Puspita, Yenny (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This research was conducted to determine the effect of finger print attendance and certification on teacher performance. In this study, the population taken was the teacher who taught at SMP NegeriKertapati with a total sample of 69 people. The methodology used in this experiment is quantitative by reviewing the information obtained from the results of the distribution of the questionnaires to measures support across the district of 3 SMP NegeriKertapati. The information gathered to obtain a relationship between the variables observed and the sample in the 3 schools are also represented simultaneously by that kind of approach. Based on this information, it really is evident that: 1. On teacher efficiency, there is an effect of finger print attendance, 2. Certification seems to have an impact on teacher performance, and 3. There is a shared impact on teacher competence at SMP NegeriSekecamatanKertapati between finger print attendance and certification. Teachers are expected to further develop their discipline and other competencies in the future, which will undoubtedly significantly improve success in the learning environment.